2007
DOI: 10.1123/jsep.29.6.706
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Makes You Feel Good, But Does Feeling Good Make You Exercise?: An Examination of Obese Dieters

Abstract: Whereas exercise-induced mood enhancement has been well documented, the relationship between mood and exercise participation is less well understood. Mood states influence evaluative judgments that could plausibly influence a decision to exercise. Further, most exercise-mood research is limited to normal weight adults in response to a single exercise session. The current investigation examines the influence of (a) morning mood on exercise, (b) exercise intensity/duration on mood enhancement, and (c) daily chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 32 publications
8
66
2
1
Order By: Relevance
“…These null findings are consistent with several other studies that also examined the affective response from physical activity in free-living settings (Wichers et al, 2012; Kanning, Ebner-Priemer, & Schlicht, 2015; Mata et al, 2012). Nevertheless, there are several studies that found a significant increase in positive affect (e.g., Gauvin et al, 1996; Carels et al, 2007) and decrease in negative affect (e.g., Gauvin et al, 1996; LePage & Crowther, 2010) after engaging in free-living physical activity. These inconsistencies could be due to the different methods used to capture physical activity levels (objectively measured vs. self-reported).…”
Section: Discussionmentioning
confidence: 99%
“…These null findings are consistent with several other studies that also examined the affective response from physical activity in free-living settings (Wichers et al, 2012; Kanning, Ebner-Priemer, & Schlicht, 2015; Mata et al, 2012). Nevertheless, there are several studies that found a significant increase in positive affect (e.g., Gauvin et al, 1996; Carels et al, 2007) and decrease in negative affect (e.g., Gauvin et al, 1996; LePage & Crowther, 2010) after engaging in free-living physical activity. These inconsistencies could be due to the different methods used to capture physical activity levels (objectively measured vs. self-reported).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the sample was a healthy cohort; however, seven studies dealt with patient groups with conditions such as affective or eating disorders (Axelson et al, 2003; Vansteelandt et al, 2007), breast cancer (Grossman et al, 2008), joint replacement (Powell et al, 2009), knee osteoarthritis (Focht et al, 2004), or chronic pain (Vendrig and Lousberg, 1997). Two studies included overweight people (Carels et al, 2007; Rofey et al, 2010). Although all of the studies made assessments in real time, the number of time points of measurement per day ranged from 1 to 30.…”
Section: Studies On Within-subject Associations Between Physical Actimentioning
confidence: 99%
“…Lower order assessment of affect has been more complex with many similar mood states and emotional response scales being developed in the absence of an underlying theoretical framework (Carels, Coit, Young & Berger, 2007;Malouff et al, 1985;Martin et al, 2000;Terry, Lane, Lane & Keohane, 1999;Watson & Clark, 1997). However, the continuing discussion concerning mood and emotion as lower order factors is beyond the scope of this study (see Watson & Clark, 1997 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity and sport has been shown to have beneficial positive effects on affect (Barkoff & Heiby, 2005;Carels et al, 2007;Jones, 2003;Russell, Pritschet, Frost, Emmett, Pelley, Black & Owen, 2003). In some instances, the difficulty in measuring affect pre and post activity seems to be timing the administration of the instrument to enable sufficient time for completion and being confident that the upcoming or previous activity is responsible for the resulting data.…”
Section: Introductionmentioning
confidence: 99%